Effects of Stromal Cell-Derived Factor-1α Secreted in Degenerative Intervertebral Disc on Activation and Recruitment of Nucleus Pulposus-Derived Stem Cells - Jinwei Ying; Zhihua Han; Shishen Pei; Linghao Su; Dike Ruan (Stem Cells International)
Stromal cell-derived factor-1α (SDF-1α) plays a significant role in mobilizing and recruiting mesenchymal stem cells (MSCs) to the sites of injury. This study investigated the potential of SDF-1α released in the degenerative intervertebral disc (IVD) to activate and recruit endogenous nucleus pulposus-derived stem cells (NPSCs) for regeneration in situ. We found SDF-1α was highly expressed and secreted by the native disc cells when cultured in the proinflammatory mediators in vitro mimicking the degenerative settings. Immunohistochemical staining also showed that the expression level of SDF-1α was significantly higher in the degenerative group compared to that in the normal group. In addition to enhancement of viability, SDF-1α significantly increased the number of NPSCs migrating into the center of the nucleotomized bovine IVD ex vivo. After the systemic delivery of exogenous PKH26-labelled NPSCs into the rats in vivo, there was a significant difference in the distribution of the migrated cells between the normal and the degenerative IVDs, which might be caused by the different expression levels of SDF-1α. However, blocking CXC chemokine receptor 4 (CXCR4) with AMD3100 effectively abrogated SDF-1α-stimulated proliferation and migration. Taken together, SDF-1α may be a key chemoattractant that is highly produced in response to the degenerative changes, which can be used to enhance the proliferation and recruitment of endogenous stem cells into the IVDs. These findings may be of importance for understanding IVD regenerative mechanisms and development of regenerative strategies in situ for IVD degeneration.